The Impact of Comorbid Diagnoses on the Course of PTSD Symptoms in Residents of Battered Women's Shelters - Fedele, Katherine M. (Psychol Trauma, 2017)
OBJECTIVE: The current investigation sought to explore the impact of the comorbidities of substance use disorder (SUD), major depressive disorder (MDD), and borderline personality disorder (BPD) on the trajectory of intimate partner violence (IPV) related posttraumatic stress disorder (PTSD) symptoms across a 6-month follow-up period in IPV survivors who seek shelter. Research has found significant comorbidity of SUD, MDD, and BPD with PTSD (see Green et al., 2006; Kessler, 1995; Pagura et al., 2010); however little to no research has explored these relationships in this unique population over time. METHOD: A sample of 147 residents of battered women's shelters completed study measures at baseline and 1-week, 3- and 6-months following shelter stay. Participants completed measures assessing for demographics, abuse, and DSM-IV-TR diagnoses. RESULTS: Results of Latent Growth Modeling (LGM) with the time-invariant covariates of SUD, MDD, and BPD yielded a significant effect of SUD (β = .002, p = .007) on the slope of IPV-related PTSD symptoms controlling for IPV victimization. Significant effects were not identified for BPD (β = .001, p > .05) or MDD (β = .002, p > .05). Results suggest IPV survivors with SUD demonstrated less improvement in PTSD symptoms over six months after they left shelter as compared to women without SUD. CONCLUSION: Findings emphasize the deleterious effects of SUD, above and beyond MDD and BPD, on IPV-related PTSD and highlight the need for assessment and treatment of SUD and PTSD simultaneously in residents of battered women's shelters.